Meta-analysis of robotic versus open pancreaticoduodenectomy in all patients and pancreatic cancer patients - Fu, Yibo; Qiu, Jiangdong; Yu, Yiqi; Wu, Danning; Zhang, Taiping (Frontiers in Surgery, 2022)
Purposes To compare perioperative outcomes of robotic pancreaticoduodenectomy (RPD) to open pancreaticoduodenectomy (OPD) using evidence from cohort studies. Methods Outcomes of interest include operative time, blood loss, R0 resection rate, lymph nodes harvested, overall complication rate, pancreatic fistula rate, delayed gastric emptying rate and 90-day mortality. Results 6 prospective studies and 15 retrospective studies were included. Five of these studies were limited to patients with pancreatic cancer. Operative time was significantly longer in RPD (WMD: 64.60 min; 95% CI: 26.89 to 102.21; p = 0.001). Estimated blood loss was lower in RPD (WMD: −185.44 ml; 95% CI: −239.66 to −131.21; p < 0.001). Overall complication rates (OR: 0.66; 95% CI: 0.44 to 0.97; p < 0.001) and pancreatic fistula rate (OR: 0.67; 95% CI: 0.55 to 0.82; p < 0.001) were both lower in RPD. Length of hospital stay was longer in OPD (WMD: −1.90; 95% CI: −2.47 to −1.33). 90-day mortality was lower in RPD [odds ratio (OR): 0.77; 95% CI: 0.45 to 0.95; p = 0.025]. Conclusion At current level of evidence, RPD is a safer alternative than OPD with regard to post-operative outcomes and blood loss. However, in terms of oncological outcomes RPD show no advantage over OPD, and the cost of RPD was higher. In general, RPD is now considered a reliable technology, but high-quality randomized controlled trial (RCT) studies are still needed to support this conclusion.